A putative role for telocytes in placental barrier impairment during preeclampsia. Issue 1 (January 2015) - Bosco, C.; Díaz, E.; Gutiérrez, R.; González, J.; Parra-Cordero, M.; Rodrigo, R.; Barja, P.
Abstract Preeclampsia (PE) is a major health problem occurring in pregnant women and the principal cause of maternal morbidity and perinatal mortality. It is characterized by alteration of the extravilli trophoblast cell migration toward the endometrial spiral arteries with a concomitant reduction in maternal blood flow in the placenta. This result in a state of ischemia–hypoxia which triggers an oxidative stress stage with production of reactive oxygen species. A cascade of cellular and molecular events leads then to endothelial dysfunction, transduction pathway signal disruption and induction of apoptosis and necrosis mechanisms and therefore a significant reduction in the amount of nutrients required for normal fetal development. Placental anchoring chorionic and stem villi present a skeleton of myofibroblasts arranged in parallel disposition to its longitudinal axis. The intraplacental blood volume is controlled by the contraction/relaxation of these myofibroblasts, promoting the delivery of nutrients and metabolites to the fetus. Recently, a new mesodermal originated cell type has been described in the villous stroma, the so named "telocytes". These cells are strategically located between the smooth muscle cells of the blood vessel wall and the myofibroblasts, and it is reasonable to hypothesize that they may play a pacemaker role, as in the intestine. This study provide new information supporting the notion that the occurrence of oxidative stress in PE is not only related to endothelial dysfunction and apoptosis of the trophoblast cells, but also involves telocytes and its putative role in the regulation of fetal blood flow and the intra-placental blood volume. Some ideas aimed at dilucidating the relationship between placental failure and the behavior of telocytes in pathological organs in adulthood, are also discussed.